Long non-coding RNA expression profiles predict clinical phenotypes in glioma - Zhang, Xiaoqin; Sun, Stella; Pu, Jenny Kan Suen; Tsang, Anderson Chun On; Lee, Derek; Man, Venus On Ying; Lui, Wai Man; Wong, Stanley Thian Sze; Leung, Gilberto Ka Kit (Neurobiology of disease, 2012)
Glioma is the commonest form of primary brain tumor in adults with varying malignancy grades and histological subtypes. Long non-coding RNAs (lncRNAs) are a novel class of non-protein-coding transcripts that have been shown to play important roles in cancer development. To discover novel tumor-related lncRNAs and determine their associations with glioma subtypes, we first applied a lncRNA classification pipeline to identify 1970 lncRNAs that were represented on Affymetrix HG-U133 Plus 2.0 array. We then analyzed the lncRNA expression patterns in a set of previously published glioma gene expression profiles of 268 clinical specimens, and identified sets of lncRNAs that were unique to different histological subtypes (astrocytic versus oligodendroglial tumors) and malignancy grades. These lncRNAs signatures were then subject to validation in another non-overlapping, independent data set that contained 157 glioma samples. This is the first reported study that correlates lncRNA expression profiles with malignancy grade and histological differentiation in human gliomas. Our findings indicate the potential roles of lncRNAs in the biogenesis, development and differentiation of gliomas, and provide an important platform for future studies. ► LncRNAs represented on Affymetrix HG-U133 Plus 2.0 array were identified. ► LncRNAs were aberrantly expressed in human glioma. ► Differential expressions of lncRNAs may correlate with malignant progression and histological differentiation in glioma.